Religijność w Księdze Kapłańskiej - Stanek, Teresa (Poznańskie Studia Teologiczne, 2009)
The Book of Leviticus appears as a compilation of fragmentary cultic and ethical prescriptions, coming from different periods of religious history of Israel. The synchronic analysis, started by Mary Douglas, proved that the editor of final version of Leviticus was a great artist, with a religious goal. Leviticus is a book that presents multiple layers of meaning. In this article the Book of Leviticus was considered from the Religionswissenschaft point of view. The text was divided on a major blocks according to its theme, and then asked what message was delivered through each one of them; and subsequently, what was message of the whole Book. Careful analysis of vocabulary, as well as the time and place of action, allow to suggest a new structure - the four final chapters might serve as the endings for three blocks of text. The theme leads the reader from the temple to the community; from the present to the future.